Research in action. An example of experimental study in marketing services - Acevedo Borrego, Adolfo (2013)
The article shows an example of application of the methodology of action research. We present the design and results of a study based on the mobile phone in the aspect of pricing decisions, it’s comparison of means for dependent samples, measuring the effect on incoming cellular telephone traffic due to changing pricing strategy, by cellular operator. In case, the customer behavior with traffic reduced incoming calls to cell phones manifests an initial problem that affected the company’s earnings. Among various alternatives, the mode change for the customer tariff suggests increase receiving phone calls, raising the incoming telephone traffic and revenue. To corroborate this hypothesis we defined a random sample of 25 clients who applied a new tariff model, on a restricted basis for a month, tracking the results through the computer system. This type of experiment is called the mean difference related populations, which is considered the same sample at different moments.